The Constructed Wetland Wastewater Treatment System, the Landscape Architect and Potentials for Philippine Use - Flor, Enrico G. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2000)
The earth's resources are dwindling and it is time for landscape architects to act as the fulcrum of environmental conservation, development, sustainability and design. Among the foreign sustainable technologies being studied right now are constructed wetlands for wastewater treatment. Its main role is to improve water quality, but it also provides lateral benefits such as scenic, recreational, wildlife, cultural and aesthetic, among others. Furthermore, the existing technologies seem to be adaptable in the Philippine setting such as the various plant materials used. With the participation of the landscape architect, the multi-use character of any constructed wetland project in the Philippines can be explored further. However, further studies are required to validate the performance of constructed wetland systems in the local setting. Once done, and with the participation of the landscape architect, another sustainable and scenic technology will be available to the people. Also, by advocating and incorporating the technology for local use, the landscape architect would have pushed further the relevance of his profession beyond aesthetic considerations.